1994
DOI: 10.1111/j.1432-1033.1994.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Calmodulin by the Epidermal‐growth‐factor‐receptor Tyrosine Kinase

Abstract: An epidermal-growth-factor(EGF)-receptor preparation isolated by calmodulin-affinity chromatography from rat liver plasma membranes is able to phosphorylate calmodulin. Calmodulin phosphorylation was enhanced 3-8-fold by EGF, was dependent on the presence of a polycation or basic protein and was inhibited by micromolar concentrations of Ca2+. Phosphate incorporation into calmodulin occurs predominantly on tyrosine residues. Partial proteolysis of phosphocalmodulin by thrombin identifies Tyr99, located in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 48 publications
6
52
0
Order By: Relevance
“…Figure 1(A) shows the phosphorylation of CaM in the absence and presence of EGF, performed in the first step of the assay in the absence of Ca 2 + (presence of EGTA) as indicated and the phosphorylation of PGT, subsequently assayed in the second step within the same reaction mixture either in the absence of Ca 2 + (EGTA) or in its presence (Ca 2 + ). As we have previously reported, the addition of Ca 2 + just before starting the phosphorylation of PGT in the second step should prevent further phosphorylation of CaM by the EGFR [17,18,33,34]. It can be observed that the phosphorylation of PGT, detected as a smear along the electrophoretic tracks, was higher when P-(Tyr)-CaM became accumulated in the first part of the sequential assay, as compared to control experiments performed in the absence of CaM.…”
Section: Egfr-phosphorylated Cam Enhances Egf-dependent Egfr Activationsupporting
confidence: 50%
See 4 more Smart Citations
“…Figure 1(A) shows the phosphorylation of CaM in the absence and presence of EGF, performed in the first step of the assay in the absence of Ca 2 + (presence of EGTA) as indicated and the phosphorylation of PGT, subsequently assayed in the second step within the same reaction mixture either in the absence of Ca 2 + (EGTA) or in its presence (Ca 2 + ). As we have previously reported, the addition of Ca 2 + just before starting the phosphorylation of PGT in the second step should prevent further phosphorylation of CaM by the EGFR [17,18,33,34]. It can be observed that the phosphorylation of PGT, detected as a smear along the electrophoretic tracks, was higher when P-(Tyr)-CaM became accumulated in the first part of the sequential assay, as compared to control experiments performed in the absence of CaM.…”
Section: Egfr-phosphorylated Cam Enhances Egf-dependent Egfr Activationsupporting
confidence: 50%
“…Histone acts as a cationic cofactor for the phosphorylation of CaM and given that, the amount of P-(Tyr)-CaM formed in the assay depends on the CaM-histone ratio used [33,34]. Upon changing this ratio, we observed that the activation of the EGFR in the presence of EGF was directly proportional to the amount of accumulated P-(Tyr)-CaM (result not shown).…”
Section: Egfr-phosphorylated Cam Enhances Egf-dependent Egfr Activationmentioning
confidence: 53%
See 3 more Smart Citations